2003
DOI: 10.1080/02615470309138
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of service users in the assessment of Diploma in Social Work students on practice placements

Abstract: The government, local authorities and academic institutions in the United Kingdom all positively support the involvement of service users in social work practice and education. Based upon research undertaken for a Master's dissertation, this article argues for such an inclusive approach. The author works for the Training and Development Services of an English Social and Caring Services department, which delivers a Diploma in Social Work course in collaboration with the local university college. This course beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Although consumer participation is recommended in all professions and mandated in some, students and health practitioner educators have expressed concerns about consumers' capacity to contribute effectively to the teaching and learning in undergraduate courses (Babu et al, 2008;Edwards, 2003;Ikkos, 2003;Morgan & Jones, 2009;O'Donnell & Gormley, 2013). This is especially true in relation to their involvement in the assessment of students.…”
Section: Concerns About Consumer Participationmentioning
confidence: 99%
“…Although consumer participation is recommended in all professions and mandated in some, students and health practitioner educators have expressed concerns about consumers' capacity to contribute effectively to the teaching and learning in undergraduate courses (Babu et al, 2008;Edwards, 2003;Ikkos, 2003;Morgan & Jones, 2009;O'Donnell & Gormley, 2013). This is especially true in relation to their involvement in the assessment of students.…”
Section: Concerns About Consumer Participationmentioning
confidence: 99%
“…Research (Edwards, 2003;Levin, 2004) has shown that service user and carer involvement in assessing practice learning has been uneven. Although there were signs of a clear trend towards greater involvement, it appeared that the process has been incremental and continues to be more informal than systematic.…”
Section: Discussionmentioning
confidence: 99%
“…Service users and carers had been involved in assessing practice learning under the DipSW but not consistently (Edwards, 2003) so the requirement for service user and carer involvement in all aspects of the degree (Department of Health, 2002b, p. 9) was an important change.…”
Section: Service User Involvementmentioning
confidence: 99%
“…Edwards (2003) does consider this issue in relation to the training of social work students but placements often constitute a significant aspect of mental health training for a much wider range of professionals. An understanding of service user and carer involvement on placements could offer crucial information to develop thinking about how meaningful involvement can be achieved and the impact that this might have on the mental health professionals of the future.…”
Section: Introductionmentioning
confidence: 98%